Elimination of Thiophenic Compounds by Cycloaddition with Ethylene for an Efficient Purification of Fuels: A DFT Study - Kanhounnon, G. Wilfried; Richard, Fréderick; KPOTIN, ASSONGBA GASTON; KOUDJINA, FRANÇOIS; KUEVI, URBAIN AMAH; ATOHOUN, B. C. A. R. (My University, 2020)
Using DFT calculations, we have investigated the cycloaddition of thiophene with ethylene, followed by desulfurization of the produced heterobicyclic molecules at 373 K. The whole reaction process has been modeled in three steps: (i) the molecule adsorption on tungsten sulfide acting as a catalyst, (ii) the cycloaddition of the adsorbed molecule with ethylene, (iii) the elimination of the sulfur atom by hydrogenation of the cycloaddition products. Cycloaddition, in the presence or in the absence of catalyst, produced a bicyclic compound including a C–S bond. Its reaction with hydrogen led to the hydrogenolysis of C–S bonds. Without catalyst, the reaction of bicyclic compounds with hydrogen led to a double hydrogenolysis producing cyclohexa-1,2-diene and hydrogen sulfur. In the presence of catalyst, the reaction took place in two steps, leading to cyclohexene. With increasing the molecular weight of compounds, cycloaddition can allow the separation between light hydrocarbons from alkyl-thiophenic molecules with distillation, knowing that boiling temperature increases with the molecular weight. Although consuming more hydrogen, the reaction with catalysts led to an unsaturated cyclic product which can improve the octane number of fuels containing them.
Keywords: Hydrotreatment · Cycloaddition · Thiophen · Tungsten sulfide